Predictors and Long‐Term Clinical Impact of Acute Stent Malapposition: An Assessment of Dual Antiplatelet Therapy With Drug‐Eluting Stents (ADAPT‐DES) Intravascular Ultrasound Substudy - Bin Wang; Gary S. Mintz; Bernhard Witzenbichler; Cristiano F. Souza; D. Christopher Metzger; Michael J. Rinaldi; Peter L. Duffy; Giora Weisz; Thomas D. Stuckey; Bruce R. Brodie; Mitsuaki Matsumura; Myong‐Hwa Yamamoto; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The impact of acute stent malapposition (ASM) on long‐term clinical outcomes in patients undergoing percutaneous coronary intervention is still controversial. We sought to evaluate predictors and long‐term clinical outcomes of ASM. Methods and Results ADAPT‐DES (Assessment of Dual Antiplatelet Therapy With Drug‐Eluting Stents) was a prospective multicenter study of 8663 patients undergoing percutaneous coronary intervention using drug‐eluting stents. In a prespecified intravascular ultrasound–guided substudy, 2072 patients with 2446 culprit lesions had post–percutaneous coronary intervention intravascular ultrasound and were classified according to the presence or absence of ASM. After intravascular ultrasound–guided percutaneous coronary intervention, the overall prevalence of ASM after successful drug‐eluting stents implantation was 14.4% per patient and 12.6% per lesion. Compared to lesions without ASM, lesions with ASM had larger in‐stent lumen areas, larger stent areas, and larger in‐stent vessel areas. A larger mean plaque area along with more attenuated plaque was observed in lesions with ASM versus lesions without ASM. Lesions with ASM had greater proximal and distal reference lumen areas and more distal, but not proximal, reference calcium compared to lesions without ASM. At 2‐year follow‐up, there was no significant difference in the incidence of cardiac death; myocardial infarction; early, late, or very late stent thrombosis; or clinically driven target lesion revascularization in patients with ASM versus those without ASM. Furthermore, ASM was not an independent predictor of 2‐year major adverse cardiac events or target lesion revascularization even when forced into the multivariate model. Conclusions In patients treated with intravascular ultrasound–guided drug‐eluting stents implantation, ASM was not associated with adverse clinical events during long‐term follow‐up including, but not limited to, stent thrombosis. Clinical Trial Registration URL: https://www.clinicaltrials.gov. Unique identifier: NCT00638794.